Influence of Social Media on Newspaper Patronage among Lecturers in University Of Nigeria, Nsukka - Ekpali Joseph Saint; Eric Msughter Aondover; Uchendu Chinelo Ebele; Timothy Ekeledirichukwu Onyejelem (Britain International for Academic Research (BIAR-Publisher), 2024)
The arrival of the internet has opened a new vista and opportunity for everyone to send messages to a wide, large, dispersed, anonymous, and heterogeneous audience, which is traditionally the duty of an organization. In this case, the situation has become a “one-to-many model”, and more so, the internet has triggered the development of social media; a platform where users meet to interact, receive and share information. In this direction, this study examined the influence of social media on newspaper patronage among lecturers in University of Nigeria Nsukka. The study is anchored on Technology Acceptance Theory and Media Richness Theory. The study adopted the survey research method because of its ability to investigate problems in realistic settings. The total population of lecturers in UNN is 2889 while the sample size is 340. A multi stage sampling technique was adopted for this study using cluster sampling and simple random sampling. Face validity was adopted for this study. The method of measuring reliability adopted for this work was the Test-Retest Method. Based on the findings, the study discovered that a large number of respondents use social media for information purposes as against the little number of those who do not access social media. The findings indicate that most of the respondents rely on social media for news very often. The study also found that there are factors that lead to accessing social media for use. From the findings, it is not out of place to conclude that the news ecosystem will continue to evolve just as distributed content will become commonplace. News organizations will have to struggle for relevance in the digital landscape.